Excitation Current Analysis of a Hydropower Station Model Considering Complex Water Diversion Pipes - Yan, D.; Zhuang, K.; Xu, B.; Chen, D.; Mei, R.; Wu, Changzhi; Wang, Xiangyu (American Society of Civil Engineers, 2017)
Â© 2017 American Society of Civil Engineers. Rapid development of the hydroelectric power industry has raised concerns about the stability of hydroturbine units among the scientific and engineering communities. Most existing approaches that model hydropower stations focus on the design of the hydroturbine governing system or on analysis of the complex forces acting on hydraulic turbine generators. These models fail to comprehensively study the impact of such forces on the stability of hydropower stations. This study provides a novel model for analyzing the stability of generators that are subjected to increasing excitation currents. The results highlight a significant difference between the dynamic response of the shafting system and governing system for values of the excitation current lower than 880 A. Conversely, the fluctuations affecting the two subsystems appear to be consistent when the excitation current exceeds 880 A. Finally, the response of the whole system appears to be subject to random vibrations when the excitation current is 1,380 A. These findings offer a useful insight into the dynamic response of hydropower systems and their safe and stable operation.